ASSESSMENT OF THE RESCORLA-WAGNER MODEL WITH EXPERIMENTAL DATA - Golubovski, Roman; Markoski, Gjorgji; Kiteva-Trencevska, Gordana; Dolnenec-Baneva, Natalija (Matematichki Bilten, 2018)
Mathematical modeling is fundamental to the modern trends in the technological development, one of which is the Biomedical Engineering. This paper depicts an application in the field of EEG processing and analysis. Specifically, extraction (filtering) of event-related wave from within the overwhelming EEG potentials, and evaluation of a mathematical model of the cognitive process in humans supported by experimentally obtained data. CNV morphology is acquired through an experimental setup and subject’s electroexpectogram (EXG) is derived. A suitable form of the Rescorla-Wagner model (basic for the classical conditioning theory) is solved as a system of differential equations, and one of the solutions is recognized to consistently match the EXG curve. At last, physiological explanation is given followed by a conclusion related to the experimentally supported mathematical model.